University Students’ Experiences in a Newly Established EMI Program: Motivations, Satisfaction, and Challenges - Muhammad Ibnu Mustofa; Diana Monita; Wini Ranti; Ixsir Eliya (Journey: Journal of English Language and Pedagogy, 2025)
The aims of the current research are threefold. First, it aimed to find out the motivations of students in Islamic education programs to choose an EMI program. Secondly, it was conducted to reveal the student satisfaction with the EMI program. Third, it sought to explore the difficulties or challenges perceived by students in the EMI program. This study employed a quantitative descriptive approach, surveying 22 students from an international class at an Islamic state university in Jogjakarta, Indonesia. The results revealed that students were mainly motivated by the need to access international publications, improve English proficiency, and enhance career prospects. Most participants felt that the program offered positive challenges, boosted motivation, and improved their vocabulary related to their courses. Additionally, many students expressed satisfaction with their lecturers' spoken English and the simplified content delivered in English. In terms of challenges, nearly half of the students reported difficulties in understanding lectures and course contents. Other challenges included writing notes and following peer discussions. These insights highlight the need for targeted support and instructional strategies to address the linguistic demands of EMI programs in the Indonesian Islamic higher education context.